2018
DOI: 10.3390/batteries4020015
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Remaining Useful Life Estimation of Lithium-Ion Battery with Optimal Multi-Level Particle Filter and Genetic Algorithm

Abstract: Prognosis and remaining useful life (RUL) estimation of components and systems (C&S) are vital for intelligent asset-integrity management. The implementation of the traditional multi-level particle filter (TRMPF) has improved prognosis when compared with the one-step traditional particle filter that depended on the first-order state equation. However, despite this improvement, the need to enhance the accuracy of fault prognosis, diagnosis and detection cannot be overemphasized. To this end, an optimal multi-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In general terms, the RUL is defined as the useful operative life of the supercapacitor before it attains the threshold level (70% or 80% of the initial capacity). Therefore, it is suggested that the supercapacitor is replaced when the threshold level is achieved [68]. The estimation of the RUL of a supercapacitor is important, as it provides crucial information by determining the occurrence of failure and eliminating issues [6,69].…”
Section: Progress Of Rul Estimation Techniques In Smsmentioning
confidence: 99%
“…In general terms, the RUL is defined as the useful operative life of the supercapacitor before it attains the threshold level (70% or 80% of the initial capacity). Therefore, it is suggested that the supercapacitor is replaced when the threshold level is achieved [68]. The estimation of the RUL of a supercapacitor is important, as it provides crucial information by determining the occurrence of failure and eliminating issues [6,69].…”
Section: Progress Of Rul Estimation Techniques In Smsmentioning
confidence: 99%
“…FIGURE 2 flow chart of the remaining useful life (RUL) prediction where f () and g() are the nonlinear transfer functions, which are going be made first-order Taylor series expansion near (x k , u k ), respectively. Then, the system state space model can be got after linearization and the final results can be calculated by a series of mathematical formulas from (15) to (20). Q and R are, respectively, the variances of w(k) and v(k).…”
Section: Introduction Of the Ekf For Importance Resamplingmentioning
confidence: 99%
“…Internal resistance, capacity, and power of the battery are used as key parameters to establish the cycle life model . And, the particle filter (PF) can be used to predict the RUL based on the experience degradation model, which is suitable for the nonlinear and non‐Gaussian system. But, the PF algorithm has poor adaptability because of the particle degradation phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated aging tests can be divided into two categories: calendar aging and cycling aging [1][2][3][4]. The behavior of an ESS during its storage is tested in calendar aging.…”
Section: Introductionmentioning
confidence: 99%